Carl J. Couch and the Iowa School : in his own words and in reflection (Emerald Publishing, 2017)
This volume includes new Iowa School founder, Carl J. Couch's previously unpublished memoir The Romance of Discovery, alongside personal reflections from friends and colleagues. It also includes an unpublished essay by Couch reflecting on his methodology and unique theoretical approach of the Iowa School of symbolic interactionism.
Keywords: Couch, Carl J.; Social interaction.; Interpersonal relations.; elektronické knihy; electronic books